Application of the Nawaz-Enscore-Ham (NEH) algorithm for flow shop scheduling in a timber factory - Muharni, Yusraini; Saeful Muttaqien, Ade Irman; Lazuardi, Hilal; Herlina, Lely; Febianti, Evi; Ilhami, Muhammad Adha; Ulfah, Maria; Hartono, Hartono (Journal Industrial Servicess, 2024)
Scheduling is essential in production systems as it manages resource allocation and ensures precise and timely operations. A timber firm produces wooden hammocks and pallets to meet the demand for wooden pallets in the domestic market using a flow shop type production flow and the First Come First Served (FCFS) method. In December 2022, there was excess capacity due to a decrease in demand. Conversely, the company experienced a shortage of capacity in January due to a significant increase in demand for pallets from several companies. This situation resulted in idle time when switching to the next task, indicating that production capability was not being utilized to its full potential. The aim of this research is to provide production scheduling proposals to minimize makespan by applying the Nawaz-Enscore-Ham (NEH) method and the Integer Linear Programming (ILP) method. The proposed production scheduling with a lower makespan has been successfully obtained in this study.